Program Aplikasi Optimalisasi Perencanaan Produksi dengan Metode Goal Programming (Kasus CV. G) - Zahedi Zahedi; I Wayan Aditya Eka Putera (ComTech: Computer, Mathematics and Engineering Applications, 2010)
Indonesia today is still a State agrarian. Thus agriculture in Indonesia always get more attention by the government. Many government programs are rolled out to support the agricultural development of Indonesia, and one of them is the fertilizer subsidy to farmers Indonesia. Fertilizer itself is very useful to nourish the soil and provide vitamins to the plants, thus increasing the amount of production generated. Therefore it is necessary fertilizer for agriculture in Indonesia. CV. G company is one of the companies that produce fertilizer. Fertilizer produced by this company is an organic fertilizer and inorganic fertilizer. Problems faced by these companies are in planning the production of fertilizer produced. Companies want to optimize the amount of production of each fertilizer, maximize revenues, minimize production costs, and simultaneously optimize the working hours of employees. To meet these objectives, this research created program package using goal programming methods. Goal programming method can provide an effective solution / equilibrium toward the goals set, and the calculation will be assisted by using the Simplex method that has been modified. This method is an extension of linear programming, linear programming which can only solve problems with a single goal while the goal programming to solve problems with multiple objectives.